2019
DOI: 10.1111/pim.12682
|View full text |Cite|
|
Sign up to set email alerts
|

Improving the immunogenicity and protective efficacy of a whole‐killed malaria blood‐stage vaccine by chloroquine

Abstract: A whole‐killed malaria blood‐stage vaccine (WKV) is promising in reducing the morbidity and mortality of malaria patients, but its efficacy needs to be improved. We found that the antimalarial drug chloroquine could augment the protective efficacy of the WKV of Plasmodium yoelii. The direct antimalarial effect of chloroquine on parasites during immunization could be excluded, as the administration of chloroquine or chloroquine plus alum every two weeks had a slight effect on parasitemia, and an immunization wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Aluminum-containing adjuvants are the most widely used clinical adjuvants, which have been demonstrated not only to directly trigger the NALP3 inflammasome but also to indirectly activate the host innate immune response by inducing the release of the endogenous danger signal uric acid (Lambrecht et al, 2009). However, we found that alum only slightly improved the immunogenicity of pRBC lysate (Fu et al, 2020). Although CpG has been reported to be able to significantly enhance the malaria parasite-specific CD4 + T responses and reduce the vaccine dose from 10 8 to 10 3 (Pinzon-Charry et al, 2010), the use of CpG as an adjuvant in humans has not been approved.…”
Section: Development Of An Appropriate Human-compatible Adjuvantcontrasting
confidence: 62%
See 1 more Smart Citation
“…Aluminum-containing adjuvants are the most widely used clinical adjuvants, which have been demonstrated not only to directly trigger the NALP3 inflammasome but also to indirectly activate the host innate immune response by inducing the release of the endogenous danger signal uric acid (Lambrecht et al, 2009). However, we found that alum only slightly improved the immunogenicity of pRBC lysate (Fu et al, 2020). Although CpG has been reported to be able to significantly enhance the malaria parasite-specific CD4 + T responses and reduce the vaccine dose from 10 8 to 10 3 (Pinzon-Charry et al, 2010), the use of CpG as an adjuvant in humans has not been approved.…”
Section: Development Of An Appropriate Human-compatible Adjuvantcontrasting
confidence: 62%
“…However, chloroquine was found to greatly promote CD8 + T cell responses against soluble antigens in vivo, through inhibiting the degradation of internalized soluble antigen in endosomes by increasing the pH of the endosomes (Accapezzato et al, 2005). Interestingly, we found that low-dose antimalarial chloroquine along with alum synergistically improved the immunogenicity of pRBC lysates by enhancing the humoral response, although chloroquine alone only had a slight effect (Fu et al, 2020). As chloroquine has been approved as safe for humans, we strongly suggest that the use of low-dose chloroquine, along with alum, should be explored to enhance the immunogenicity of WKV.…”
Section: Development Of An Appropriate Human-compatible Adjuvantmentioning
confidence: 73%
“…In fact, chloroquine together with an adjuvant (i.e. alum) increases the protective efficacy of whole-killed blood-stage vaccines via humoral immune responses due to an expansion of GC B cells and class‐switch recombination [ 65 ]. A synthetic analog of malarial hemozoin has been proposed to be a universal adjuvant [ 66 ].…”
Section: Introductionmentioning
confidence: 99%